2007
DOI: 10.1124/mol.107.037002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Kinase Cζ and Its Adaptor Protein p62 in Voltage-Gated Potassium Channel Modulation in Pulmonary Arteries

Abstract: Voltage-gated potassium (K V ) channels play an essential role in regulating pulmonary artery function, and they underpin the phenomenon of hypoxic pulmonary vasoconstriction. Pulmonary hypertension is characterized by inappropriate vasoconstriction, vascular remodeling, and dysfunctional K V channels. In the current study, we aimed to elucidate the role of PKC and its adaptor protein p62 in the modulation of K V channels. We report that the thromboxane A 2 analog 9,11-dideoxy-11␣,9␣-epoxymethano-prostaglandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…In addition, sequestosome1/p62, a stress-inducible protein regulated by the redox-sensitive transcription factor Nrf2, was shown to serve as a scaffold protein acting as a physical link in the assembly of PKCζ-sequestosome1/p62-potassium channel complexes and to facilitate phosphorylation of K V β by PKCζ, which induces inhibition of pulmonary arterial K V 1.5 channels [41]. Consistent with this and similar to findings in PKCζ −/− PASMCs, U46619 fails to inhibit K V currents in PASMCs deficient for sequestosome1/p62 [40]. Collectively, these data provide evidence for a modulatory role of sequestosome1/ p62 in the functional activity of K V 1.5.…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Csupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, sequestosome1/p62, a stress-inducible protein regulated by the redox-sensitive transcription factor Nrf2, was shown to serve as a scaffold protein acting as a physical link in the assembly of PKCζ-sequestosome1/p62-potassium channel complexes and to facilitate phosphorylation of K V β by PKCζ, which induces inhibition of pulmonary arterial K V 1.5 channels [41]. Consistent with this and similar to findings in PKCζ −/− PASMCs, U46619 fails to inhibit K V currents in PASMCs deficient for sequestosome1/p62 [40]. Collectively, these data provide evidence for a modulatory role of sequestosome1/ p62 in the functional activity of K V 1.5.…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Csupporting
confidence: 77%
“…Using a PKCζ pseudosubstrate inhibitory peptide, COGOLLUDO et al [39] provided evidence for the role of this kinase as a link between thromboxane endoperoxide receptor activation and K V channel inhibition. The requirement for PKCζ in mediating TXA2-induced effects on K V current was further confirmed by the same group using PKCζ −/− pulmonary arteries [40]. In addition, sequestosome1/p62, a stress-inducible protein regulated by the redox-sensitive transcription factor Nrf2, was shown to serve as a scaffold protein acting as a physical link in the assembly of PKCζ-sequestosome1/p62-potassium channel complexes and to facilitate phosphorylation of K V β by PKCζ, which induces inhibition of pulmonary arterial K V 1.5 channels [41].…”
Section: Potassium Channels In Regulation Of Cell Proliferation and Cmentioning
confidence: 58%
“…Another interesting redox-related feature of K v channels is their reversible inactivation under hypoxic conditions [5,6,62] (Fig. 1B).…”
Section: Interaction Of Sqstm1 With K V β Subunitsmentioning
confidence: 97%
“…The modifications of K v channels by protein kinases affect both the expression and the activity of K v channels (reviewed by Vacher and Trimmer) [7]. Two different kinases, aPKCs and Lck, are involved in oxygen-sensing mechanisms in pulmonary arterial smooth muscle cells [62] and T lymphocytes [6], respectively (Fig. 1B).…”
Section: Interaction Of Sqstm1 With K V β Subunitsmentioning
confidence: 98%
“…Similarly, Cogolludo et al (14) reported that thromboxane A 2 -induced inhibition of K V currents in isolated rat PASMCs are attenuated by the general PKC inhibitors staurosporine, calphostin C, and Gö 6983; however, the effect of thromboxane A 2 is not blocked by bis-indolylmaleimide or the conventional PKC inhibitor Gö 6976 and can be prevented by the selective PKCz pseudosubstrate inhibitor (14). These investigators further showed that Gö 6976 blocks serotoninevoked inhibition of native K V currents in rat PASMCs and human K V 1.5 currents stably expressed in LTK cells (15), and PKCz gene deletion prevents thromboxane A 2 -induced inhibition of K V currents in isolated mouse PASMCs (54). These data further support the concept that PKCe is involved in the hypoxic inhibition of K V channels and also suggest that PKCe and PKCz may differentially mediate agonist-induced responses in PASMCs.…”
Section: Ros-dependent Hypoxic Increases In [Camentioning
confidence: 99%